Development of integrated supply chain system in manufacturing industry - Sulaiman, Shamsuddin; Aldeehani, Ahmaad Kadmouse; Alhajji, Mohammad Sh I A M I; Abdul Aziz, Faieza (IOS Press, 2021)
This paper presents the model of integrated halal supply chain in food manufacturing industries. There is global increase in the demand for halal products by Islamic countries as well as by non-Islamic countries. Halal food consumers are presently more alert and concern about the integrity of Halal status. Furthermore, they also curious about all the activities involved along the supply chain whether the products that they purchased were truly halal from the beginning to the end. The need of halal supply chain is crucial in ensuring that the concept of halal is not only applicable for the food itself but also for the whole supply chain starting from the farm to the customer. This project attempts to develop an integrated halal supply chain system that can be used by food manufacturers that are developing halal products for better productivity and quality. The identified supply chain components are human resources, process, environment, accreditations, logistics and traceability.